PENGEMBANGAN MEDIA PEMBELAJARAN MATERI TEKS NEGOSIASI BERBASIS POWERPOINT INTERAKTIF - Ala’ Imroatana; Nisaul Barokati Selirowangi; Anisa Ulfah (Pendidikan Bahasa dan Sastra Indonesia, 2022)
This study aims to develop learning media in learning Indonesian negotiation text material by measuring the quality of the learning media. This research was tested at SMK Wachid Hasyim Maduran. The subject of the study was a class X student majoring in Multimedia with a total of 37 students. This type of research is research and development, which adapts to the Borg and Gall development procedure which consists of 10 stages but is only used by 6-stage researchers due to time constraints. The results showed that: the development of interactive powepoint-based learning media products has gone through the assessment stage by media expert lecturers, material expert lecturers, practitioners (teachers), field trials (students). The assessment by media expert lecturers got a percentage of 88% including the decent category. Assessment by material expert lecturers gets a percentage of 80% including the decent category. Practicality assessment by teachers gets a percentage of 100% belonging to the category of feasible. The results of the student trial, the percentage of scores obtained by 84% is included in the decent category. The overall scoring average gets a final score of 88% with a decent category. Based on the results of the nlai, it means that the interactive powepoint-based learning media that has been developed is suitable for use.